Studies on Schismatoglottis (Araceae) of Borneo IV : Preliminary observations on spathe senescence mechanics in Schismatoglottis Zoll. & Moritzi in Sarawak, Malaysian Borneo - Peter C., Boyce; Wong, Sin Yeng (International Aroid Society Inc., 2007)
Recent alpha-taxonomic studies of Schismatoglottis Zoll. & Moritzi provide a sufficiently stable framework to facilitate taxonomically robust multidisciplinary research, notably molecular phylogenetic, ecological and phenological studies including analyses of morphology adaptations to specialized ecology (in particular rheophytism), and comparison of mechanical processes linked to pollination strategies (notably spathe senescence)...